Molecular phylogeny and systematics of the genus Draba (Brassicaceae) and identification of its most closely related genera - Jordon-Thaden, Ingrid; Hase, Irina; Koch, Marcus (Molecular phylogenetics and evolution, 2010)
Phylogenetic analyses of sequence data from the internal transcribed spacer regions of the nuclear ribosomal DNA (ITS) and the plastid trnL-F region were conducted to reconstruct the phylogenetic history of Draba and related genera. Out of the ∼370 Draba species, 169 geographically and morphologically representative species are sampled here, including such “controversial” segregates as Abdra, Arabis, Athysanus, Drabopsis, Erophila, Graellsia, Heterodraba, Schivereckia and Tomostima. Phylogenetic analyses of the combined ITS and trnL-F markers indicate that Draba represents a monophyletic evolutionary lineage within the tribe Arabideae, but previously proposed infrageneric classification systems are mostly artificial (i.e. do not reflect true evolutionary history). Draba muralis formed an independent genus, possibly between Draba and Arabis, whereas D. hystrix fell outside Draba and was closely associated with Arabis. The New World annual, lowland Draba, D. platycarpa, D. reptans, D. cuneifolia, D. australis, D. arabidoides, (section Abdra) and D. brachycarpa and D. aspera (section Tomostima), appear to be independent genera that fall outside Draba and are monophyletic with the endemic North American Heterodraba unilateralis and Athysanus pusillus. Graellsia hederifolia and Erophila verna appear to be earlier diverging Draba species, with weak evidence of ancient hybridization in G. hederifolia. Core Draba species were organized into three major groups that encompass the segregate genera Drabopsis and Schivereckia. The three groups have geographic significance: Group I-Europe to Iran; Group II-North and South American Cordillera; Group III-Asian, Arctic, and Beringian. These three groups also have significant petal color and base chromosome level similarities. We also found that Arabis rimarum is a synonym for Draba aucheri, and is well within Group I of Core Draba. Therefore, we propose that many of the lowland and coastal temperate species often associated with Draba should be excluded from that genus. The compilation of these data indicate that true Draba are highly migrating arctic and higher alpine species that are most often perennial with white petals and n = 8 as plesiomorphic characters.